1982
DOI: 10.1172/jci110521
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Enzymatic Comparison of Human Cardiac Muscle Myosins Isolated from Infants, Adults, and Patients with Hypertrophic Cardiomyopathy

Abstract: A B S T R A C T Human cardiac ventricular myosins were prepared from autopsy samples from nine adults, seven infants, and from surgical specimens from seven patients undergoing left ventricular septal myectomy for obstructive hypertrophic cardiomyopathy. Infant myosin differed from adult myosin in two important characteristics: (a) t-30% of the 27,000-dalton myosin light chain is replaced by a 28,000-dalton light chain, and (b) the actin-activated myosin MgATPase activity of infant myosin is significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
2

Year Published

1984
1984
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 36 publications
4
29
2
Order By: Relevance
“…Rodents undergo a developmental change from ␤-to ␣-MHC as the dominant isoform, and then during hypertrophy or myocardial failure express as the dominant isoform ␤-MHC (41). Since most previous studies (35,36,38,39) had suggested that human ventricular myocardium does not express a biologically significant amount of ␣-MHC and therefore does not undergo an isoform change in hypertrophy or failure, the MHC isogene expression data in this report and in our companion paper (43) were unanticipated. In fact, as originally designed the only reason MHC isogene expression was measured in the current study was to provide a method of normalization of other mRNAs.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Rodents undergo a developmental change from ␤-to ␣-MHC as the dominant isoform, and then during hypertrophy or myocardial failure express as the dominant isoform ␤-MHC (41). Since most previous studies (35,36,38,39) had suggested that human ventricular myocardium does not express a biologically significant amount of ␣-MHC and therefore does not undergo an isoform change in hypertrophy or failure, the MHC isogene expression data in this report and in our companion paper (43) were unanticipated. In fact, as originally designed the only reason MHC isogene expression was measured in the current study was to provide a method of normalization of other mRNAs.…”
Section: Discussionmentioning
confidence: 64%
“…In humans, ␣-and ␤-MHC are closely related isogenes positioned sequentially on chromosome 14 (34). Although a substantial amount of ␣-MHC is present in human atrial myocardium (35)(36)(37), in human ventricular myocardium most previous studies have not detected significant (Ͼ 10%) ␣-MHC expression at the protein or mRNA levels (35,36,38,39). Our data indicate that there is substantial expression of ␣-MHC mRNA in nonfailing ventricular myocardium, and then a profound decrease in expression in myocardial failure.…”
Section: Discussionmentioning
confidence: 99%
“…In response to chronic heart overload in rodents, a shift in MHC occurred with an increase in the slow MHC isoform V3 and a decrease in the fast MHC isoform VI (26), Similar changes have been noted in the human atrial smooth muscle but not in ventricular muscle (7,23). A change in MHC isoform distribution has been seen in the rodent ventricle with hypothyroidism and in skeletal muscle after hypertroph y of chicken slow muscle from repeated use (19,27).…”
Section: Newborn Fundusmentioning
confidence: 73%
“…The formation of such a molecule in the overloaded heart reduces contractility by lowering the rate of interaction between the actin and myosin filaments. However, this concept is not generally accepted, especially due to controversial data obtained from the diseased human heart (19,33,(47)(48)(49)(50)(51).…”
Section: Myofibrillar Assembly In Congestive Hfmentioning
confidence: 99%